Analysis of Cultural Introduction in English Teaching in Chinese Senior School - Peilun, Gao; Jiawei, Lim (International Journal of Psychosocial Rehabilitation, 2020)
With the continuous deepening of the process of globalization, China’s connections with other countries in the world have become more intensive. Under this social background, a large number of comprehensive external exchange talents are urgently needed. However, in the current English teaching of Chinese senior school, the introduction of cultural factors is insufficient. In English teaching practice, teachers pay more attention to the cultivation of students’ Basic English skills without paying too much attention to cultural factors.